PENGARUH KARAKTERISTIK PERUSAHAAN, TATA KELOLA PERUSAHAAN, DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK - Richa, Yuniarwati (Jurnal Paradigma Akuntansi, 2020)
The purpose of this study is to examine the analysis of the influence of company characteristics, corporate governance, and sales growth on tax avoidance of manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Samples were selected using 70 purposive sampling methods. The data processing technique uses E-views application version 10 and  Microsoft  Excel  2016.  The  results  of  this  study  indicate  that  partially  company characteristics and sales growth have no  positive effect on tax avoidance, while corporate governance has a negative effect on tax avoidance, but simultaneously, research this study shows the characteristics of the company, corporate governance, and sales growth have a positive effect on tax avoidance.